Analysis of Logical Basis of Knowledge in Frege’s Philosophy - Aukštuolytė, Nijolė (Problemos, 2000)
The paper discusses Frege’s contribution to solving the problem of cognitive contents formalization. The state and needs of mathematics have led the author to analyse the general principles of thought and focused his efforts on the sphere of logics. Frege’ss research is based on the assumption that logical thought analysis is possible only through logical language analysis. The article points out stresses that the author’s interest in language is indirect. It is based upon the idea that language conveys knowledge in a certain way. The paper analyses Frege’s outline of mathematical logical construction. The language of formulas developed by Frege as a certain structure acquires a fundamental value of a method in the context of his philosophical research. This induced Frege to acknowledge the significance of the formal aspect in cognition. Differences in linguistic expression of a thought turned Frege’s attention to cognitive value of symbolization. This gave rise to the problem of differentiating between the sense and the meaning. By relating the sense and the meaning to the sentence structure Frege directs logical analysis towards semantic problems. These Frege’s ideas influenced further attempts of philosophers to study the potentialities of our cognition within the range of meaningful language.
Keywords: mathematics; sense; meaning